The study of life expectancy in hysterectomized women in Semnan Amir Al Momenin Hospital in 2017 - Elham Saffarieh; Reza Ahmadi; Ramin Pazoki; Azadeh Yousefnezhd; Reyhaneh Yousefi-Sharami (Journal of Family Medicine and Primary Care, 2020)
Introduction: Hysterectomy as kind of surgery in which the uterus is removed, is carried out in a very high number around the world. Uterus is important because of its impact on feminism and fertility, so the exit of this important organ can lead to many physical and mental disorders. These mental disorders can affect the quality of life of patients and ultimately lead to a reduction in the hope of their lives. Materials and Methods: This study was cross sectional on 50 women under hysterectomy referred to the Semnan Amir-Al-Momenin hospital in 2017, in which patients were evaluated in terms of effective subsets of life expectancy that were determined from the angle of view of miller questionnaire, and finally the data were analyzed by SPSS v. 19. Results: The results showed that there is no significant difference between hope to life before and after hysterectomy in those who underwent hysterectomy. The results of our study showed that age, occupation, and education factors in patients who participated in this study did not have any meaningful relation with life expectancy after hysterectomy surgery and there was also a statistically significant correlation between the scores of hope for life before hysterectomy with the rate of education in individuals. Conclusion: Hysterectomy does not affect the patients' quality of live and don't reduce the hope of living in people who underwent surgery.